NEUROPSYCHOLOGICAL AND EMOTIONAL CORRELATES OF CHANTING VISHNU SAHASRANAMAM: AN EMPIRICAL STUDY ON MIDDLE-AGED ADULTS - Puja Dawar Rao (The Bioscan, 2025)
The goal of this study is to understand the neuropsychological and emotional effects of chanting Vishnu Sahasranamam, an utmost revered Hindu mantra in middle aged adults. The goals are to determine whether such practice improves the brain's activity as well as emotional regulation and cognitive performance, focusing less on anxiety reduction, stress management, and possible benefits of mindfulness. A qualitative methodology was used for the study and in depth semi structured interviews were done with people who participate in chanting (for a long time) quite often. Personal accounts of emotional well-being, cognitive change and mindfulness experience are identified as essential data points, all of which were analysed by Thematic Analysis. The research looks into the psychological metrics such as anxiety and emotional regulation and provide a deep insight into the relationship between the concepts of spiritual practices and modern psychology theories. The findings show that repeated reading of Vishnu Sahasranamam impacts positively the level of anxiety and stress and improves mindfulness and emotional resilience. The participants reported a better cognitive clarity and a sense of clear mind, which further promotes overall mental wellness. It emphasizes the possibility of including some ancient spiritual practices into the modern psychological interventions, a bridge between historical emotional management practices and the present mental health services. These results suggest important future work to determine how such spiritual practices can be therapeutic for the purpose of psychological wellbeing.